2020
DOI: 10.3389/fvets.2020.591437
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic and Histopathological Characteristics of 13 Equine and 10 Feline Oral and Sinonasal Squamous Cell Carcinomas

Abstract: Squamous cell carcinoma (SCC) is the most common equine sinonasal and feline oral tumour. This study aimed to describe the computed tomographic and histopathological characteristics of equine and feline SCC. Thirteen horses and 10 cats that had been histopathologically diagnosed with oral or sinonasal SCC and had undergone computed tomography (CT) of the head were retrospectively included in the study. CT characteristics of the mass and involved structures were noted. Histological examinations were evaluated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Few studies report SCC in uncommon locations of the head and throat regions in equine patients. A recent case series reporting the CT appearance of 13 equine oral and sino‐nasal SCC identified the paranasal sinuses as the mass centre in the majority of cases; in this study, alternative locations were the mandible and the tongue, but none of the identified masses were centred on the pharyngeal region (Strohmayer et al, 2020).…”
Section: Discussionmentioning
confidence: 54%
“…Few studies report SCC in uncommon locations of the head and throat regions in equine patients. A recent case series reporting the CT appearance of 13 equine oral and sino‐nasal SCC identified the paranasal sinuses as the mass centre in the majority of cases; in this study, alternative locations were the mandible and the tongue, but none of the identified masses were centred on the pharyngeal region (Strohmayer et al, 2020).…”
Section: Discussionmentioning
confidence: 54%
“…Due to its infiltrative nature, it is plausible that the current neoplasm represents the local extension from a primary neoplasm originating from either the oral or respiratory mucosa, whose primary site has not been appreciated during post‐mortem examination. This tumour exhibited high grade malignancy, with the histologic malignancy score of 23 out of 24 following the grading system described by Strohmayer et al (2020), which is equivalent to grade IV on the human malignancy grading system described by Anneroth et al (1987). This is consistent with the findings of a review of equine SCCs, where most horses (13/14) had categorisation as grade 3 or above with a highly invasive nature (Strohmayer et al, 2020).…”
Section: Discussionmentioning
confidence: 92%
“…This tumour exhibited high grade malignancy, with the histologic malignancy score of 23 out of 24 following the grading system described by Strohmayer et al (2020), which is equivalent to grade IV on the human malignancy grading system described by Anneroth et al (1987). This is consistent with the findings of a review of equine SCCs, where most horses (13/14) had categorisation as grade 3 or above with a highly invasive nature (Strohmayer et al, 2020).…”
Section: Discussionmentioning
confidence: 92%
“…Precise diagnosis via CT has been emphasized in order to avoid unviable treatment approaches [27]. Malignant and benign tumors of the nasal and paranasal sinuses including squamous cell carcinoma, undifferentiated carcinoma, hemangiosarcoma, nasal adenocarcinoma, myxoma, chondroblastic osteosarcoma, anaplastic sarcoma, and fibro-osseous lesions have been described [28][29][30][31]. Henninger et al provided detailed CT descriptions regarding the most common features of sinusitis and alveolitis [32].…”
Section: Clinical Applicationsmentioning
confidence: 99%